Answer
The equation in point slope form is
y + 1 = 2 (x + 9)
Simplifying further, we have
y + 1 = 2x + 18
y = 2x + 18 - 1
y = 2x + 17
Step-by-step explanation
The general form of the equation in point-slope form is
y - y₁ = m (x - x₁)
where
y = y-coordinate of a point on the line.
y₁ = This refers to the y-coordinate of a given point on the line
m = slope of the line.
x = x-coordinate of the point on the line whose y-coordinate is y.
x₁ = x-coordinate of the given point on the line
We are given that the slope = m = 2
The point is (x₁, y₁) = (-9, -1)
x₁ = -9
y₁ = -1
y - y₁ = m (x - x₁)
y - (-1) = 2 [x - (-9)]
y + 1 = 2 (x + 9)
Simplifying further, we have
y + 1 = 2x + 18
y = 2x + 18 - 1
y = 2x + 17
Hope this Helps!!!